Heterostructured γ-Fe2O3/FeTiO3 magnetic nanocomposite: An efficient visible-light-driven photocatalyst for the degradation of organic dye. (November 2022) - Subha, N.; Mahalakshmi, M.; Monika, S.; Senthil Kumar, P.; Preethi, V.; Vaishnavi, G.; Rajabhuvaneswari, A.
Abstract: The catalyst recovery is the major concern in commercialization of photocatalysts for the industrial effluent treatment process. To overcome this major issue, Fe2 O3 based magnetic photocatalytic heterostructure ɣ-Fe2 O3 /FeTiO3 nanocomposite was synthesized by hydrothermal method. Fe2 O3 is the cheapest visible active magnetic photocatalytic material, but it has the limitation of fast e − /h + recombination. Titanium (Ti) was loaded on γ-Fe2 O3 to overcome this issue. The loaded Ti has grown as FeTiO3 on the surface of ɣ-Fe2 O3 nanocrystals and emerged as heterostructure ɣ- Fe2 O3 /FeTiO3 nanocomposites, which was confirmed by XRD and TEM results. The loading concentration of Ti on γ-Fe2 O3 was optimized to achieve the maximum photocatalytic efficiency without compromising the magnetic property of γ-Fe2 O3 to facilitate the magnetic separation. DRS-UV spectra revealed the strong visible light response of γ- Fe2 O3 /FeTiO3 nanocomposite. The photocatalytic efficiencies of the synthesized materials were evaluated using methylene blue (MB) as a model pollutant under sunlight. The built-in electric field between p-n junction between FeTiO3 and Fe2 O3 and type II charge transfer mechanism extended the lifetime of the charge carriers at the heterojunction of γ- Fe2 O3 /FeTiO3, which was confirmed by PL spectra. The vibrating sample magnetometer (VSM) study revealed the decreasing magnetization, coercivity (Hc), and retentivity (Mr) of γ-Fe2 O3 with increasing concentration of Ti. 92% of the used-up 20 wt% Ti loaded γ-Fe2 O3 /FeTiO3 magnetic nanocomposite was recovered from the treated wastewater using an electromagnet. Both magnetic properties and efficiency of the nanocomposite increased up to 20 wt% of Ti loading, beyond that decreased due to the increasing composition of antiferromagnetic FeTiO3 and the increasing number of defect sites as recombination centers. Hence, 20 wt% loading of Ti was concluded as the optimum to enhance the efficiency and to retain the magnetic properties. This work aims the commercialization of magnetic photocatalytic materials for the industrial effluent treatment. Graphical abstract: Image 1 Highlights: γ-Fe2 O3 /FeTiO3 heterostructured magnetic nanocomposite was synthesized by hydrothermal method. The lifetime of the charge carriers was extended by p-n junction and type II charge transfer mechanism. γ-Fe2 O3 catalyst recovery decreased beyond 20 wt% of Ti loading due to the increase of antiferromagnetic FeTiO3 . Complete degradation of methylene blue dye was achieved within 2 h under solar light. 92% catalyst recovery was attained for 20 wt% Ti loaded γ-Fe2 O3 /FeTiO3 magnetic nanocomposite.